Parenting and depressive symptoms among adolescents in four Caribbean societies - Lipps, Garth; Lowe, Gillian A; Gibson, Roger C; Halliday, Sharon; Morris, Amrie; Clarke, Nelson; Wilson, Rosemarie N (My University, 2012)
Abstract Background The strategies that parents use to guide and discipline their children may influence their emotional health. Relatively little research has been conducted examining the association of parenting practices to depressive symptoms among Caribbean adolescents. This project examines the association of parenting styles to levels of depressive symptoms among adolescents in Jamaica, the Bahamas, St. Kitts and Nevis, and St. Vincent. Methods Adolescents attending grade ten of academic year 2006/2007 in Jamaica, the Bahamas, St. Vincent, and St. Kitts and Nevis were administered the Parenting Practices Scale along with the BDI-II. Authoritative, Authoritarian, Permissive and Neglectful parenting styles were created using a median split procedure of the monitoring and nurturance subscales of the Parenting Practices Scale. Multiple regression analyses were used to examine the relationships of parenting styles to depressive symptoms. Results A wide cross-section of tenth grade students in each nation was sampled (nand#8201;=and#8201;1955; 278 from Jamaica, 217 from the Bahamas, 737 St. Kitts and Nevis, 716 from St. Vincent; 52.1% females, 45.6% males and 2.3% no gender reported; age 12 to 19 years, meanand#8201;=and#8201;15.3 yrs, sdand#8201;=and#8201;.95 yrs). Nearly half (52.1%) of all adolescents reported mild to severe symptoms of depression with 29.1% reporting moderate to severe symptoms of depression. In general, authoritative and permissive parenting styles were both associated with lower levels of depressive symptoms in adolescents. However, the relationship of parenting styles to depression scores was not consistent across countries (pand#8201;andlt;and#8201;.05). In contrast to previous research on Caribbean parenting, caregivers in this study used a mixture of different parenting styles with the two most popular styles being authoritative and neglectful parenting. Conclusions There appears to be an association between parenting styles and depressive symptoms that is differentially manifested across the islands of Jamaica, the Bahamas, St. Kitts and Nevis and St. Vincent.